2018
DOI: 10.18632/oncotarget.25481
|View full text |Cite
|
Sign up to set email alerts
|

Klotho inhibits EGF-induced cell migration in Caki-1 cells through inactivation of EGFR and p38 MAPK signaling pathways

Abstract: Klotho is a single-pass transmembrane protein with documented anti-cancer properties. Recent reports have implicated Klotho as an inhibitor of transforming growth factor β1 induced cell migration in renal fibrosis. Overexpression of epidermal growth factor receptor (EGFR) is known to promote tumor initiation and progression in clear-cell renal cell carcinoma (cRCC). We tested our hypothesis that Klotho inhibits EGF-mediated cell migration in cRCC by interfering with the EGFR signaling complex and mitogen-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Among these cytokines, EGFR was upregulated for 13.72‐folds in WPMY‐HI vs WPMY‐1 groups. EGFR was the most abundant and frequently activated in various diseases (malignant and benign) and was reported to regulate the EMT and wound healing . EMT plays an important role in the development of proper re‐epithelialization during the wound healing .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these cytokines, EGFR was upregulated for 13.72‐folds in WPMY‐HI vs WPMY‐1 groups. EGFR was the most abundant and frequently activated in various diseases (malignant and benign) and was reported to regulate the EMT and wound healing . EMT plays an important role in the development of proper re‐epithelialization during the wound healing .…”
Section: Resultsmentioning
confidence: 99%
“…EGFR was the most abundant and frequently activated in various diseases (malignant and benign) and was reported to regulate the EMT and wound healing. [27][28][29] EMT plays an important role in the development of proper re-epithelialization during the wound healing. 30 Next, we isolated exosomes from WPMY-1 and WPMY-HI cell culture supernatant and characterized them with the TEM and NTA ( Figure 3C and 3D).…”
Section: Shallow Heat Injury Activated Prostate Stromal Cells and Umentioning
confidence: 99%
“…The exact mechanism of this phenomenon is worth pursuing, and it could be related to the impaired migratory properties of these cells. 42 Interfering with the EGFR-MAPK signalling pathway can lead to such morphologic changes by increasing cell-cell contacts profoundly stabilising focal adhesions. 43 Therefore, it seems that the loss of motility may be induced by blocking EGFR-MAPK signalling, further modulating the cell-matrix and simultaneously enhancing cell-cell interactions.…”
Section: Discussionmentioning
confidence: 99%
“…43 Therefore, it seems that the loss of motility may be induced by blocking EGFR-MAPK signalling, further modulating the cell-matrix and simultaneously enhancing cell-cell interactions. 42 Malignant cells are capable of communicating with neighbouring cells, as well as the tumour microenvironment by forming tunnelling nanotubes (TNT). 44,45 Intercellular exchange of organelles, vesicles and signalling molecules can occur, which mediates the passage of resistance and the insensitivity to small-molecule drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that WIPI1 is associated with the lysosomal degradation of cytoplasmic components during starvation-induced autophagy [40]. Since WIPI1 is strictly involved in the phosphorylation of MAPK 1/3 [41] and klotho acts as an inhibitory modulator of MAPK signaling pathways [42], it is highly likely that the role of klotho in Golgi-mediated response in immunosenescent monocytes results from this loop. However, further studies need to be conducted to elucidate fully these interactions.…”
Section: Discussionmentioning
confidence: 99%